2015
DOI: 10.1186/s10194-015-0588-3
|View full text |Cite
|
Sign up to set email alerts
|

Repeated tender point injections of granisetron alleviate chronic myofascial pain - a randomized, controlled, double-blinded trial

Abstract: BackgroundSerotonin (5-HT) mediates pain by peripheral 5-HT3-receptors. Results from a few studies indicate that intramuscular injections of 5-HT3-antagonists may reduce musculoskeletal pain. The aim of this study was to investigate if repeated intramuscular tender-point injections of the 5-HT3-antagonist granisetron alleviate pain in patients with myofascial temporomandibular disorders (M-TMD).MethodsThis prospective, randomized, controlled, double blind, parallel-arm trial (RCT) was carried out during at two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 58 publications
1
29
0
1
Order By: Relevance
“…Granisetron has a long half-life since it is metabolized in the liver. A total of 0.5 mL of granisetron (Gra; Kytril ® , 1 mg/mL, Roche, Stockholm, Sweden) and placebo (isotonic saline, 9 mg/mL) was used as in previous studies from this group [24, 41, 42]. The same infusion rate as for the HS injections (0.02 mL/s) was used, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Granisetron has a long half-life since it is metabolized in the liver. A total of 0.5 mL of granisetron (Gra; Kytril ® , 1 mg/mL, Roche, Stockholm, Sweden) and placebo (isotonic saline, 9 mg/mL) was used as in previous studies from this group [24, 41, 42]. The same infusion rate as for the HS injections (0.02 mL/s) was used, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies have also shown that 5-HT 3 antagonists are effective analgesics for various pain conditions, such as TMD myalgia, localized trapezius myalgia and fibromyalgia [2124]. However, in most clinical trials a great proportion of the patients, regardless of diagnosis, do not respond to 5-HT 3 antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…Risk of bias was very heterogeneous among studies. Using Cochrane Collaboration's tool, nine studies were classified as low risk of bias, 13 as unclear and 20 as high risk of bias . The higher risk of bias was reporting bias.…”
Section: Resultsmentioning
confidence: 99%
“…For example, there are clinical data demonstrating that setrons exert analgesic effect on both extracranial pain syndromes and various orofacial pain . Setrons have been reported to display analgesic, anti‐allodynic and anti‐hyperalgesic activities in animal models not only of non‐trigeminal, but also of trigeminal nociception .…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are clinical data demonstrating that setrons exert analgesic effect on both extracranial pain syndromes 5,6 and various orofacial pain. 7,8 Setrons have been reported to display analgesic, anti-allodynic and anti-hyperalgesic activities in animal models not only of non-trigeminal, 9,10 but also of trigeminal nociception. [11][12][13] The latter is of particular interest since the trigeminal Summary One way to expand the existing range of anti-migraine drugs seems to be the search for pharmacological agents with anti-cephalalgic properties among medicines approved for clinical indications other than migraine.…”
Section: Introductionmentioning
confidence: 99%